2012
DOI: 10.2341/11-256-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matrix Metalloproteinase Synthetic Inhibitors on Dentin Microtensile Bond Strength of Resin Cements

Abstract: Clinical RelevanceApplication of metalloproteinase synthetic inhibitors such as 2% chlorhexidine does not compromise immediate dentin bond strength of self-adhesive resin cements. The application of 24% ethylenediamine tetra-acetic acid (EDTA) gel increases dentin bond strength when self-adhesive resin cements containing methacrylated phosphoric acid ester monomers are used. Since EDTA is also considered a synthetic matrix metalloproteinase inhibitor, 24% EDTA gel might be a simple alternative to be used in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…The results of this research demonstrated that the use of CHX did not affect the immediate bond strength, compared with the group that did not receive pre-treatment (control group), a result consistent with previous studies [2,14,17,20,21]. However, dentin irradiation with Nd:YAG negatively affected immediate and long-term bond strength to dentin.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this research demonstrated that the use of CHX did not affect the immediate bond strength, compared with the group that did not receive pre-treatment (control group), a result consistent with previous studies [2,14,17,20,21]. However, dentin irradiation with Nd:YAG negatively affected immediate and long-term bond strength to dentin.…”
Section: Discussionsupporting
confidence: 89%
“…The improvement of mechanical properties for RelyX Unicem with delayed light curing may be explained by increased contact of the material with moisture of the root dentin during the curing process. 48 Water plays a critical role in the effectiveness of a selfadhesive resin cement's curing process and bonding characteristics. 48 Additionally, the longer duration…”
Section: Discussionmentioning
confidence: 99%
“…They assumed that such precipitates work as a contaminant, precluding the interaction between mineralized dentin and the self‐adhesive cement RelyX U100 (3M ESPE, Seefeld, Germany) , and may explain the more porous interface between the named cement and dentin . However, while Di Hipólito and co‐workers observed simultaneous significant bond strength reduction in CHX‐treated groups , such reduction was not seen in another study using the same self‐adhesive cement . In addition, Lindblad and co‐workers found the highest immediate and long‐term post bond strength with CHX pretreatment using a related self‐adhesive cement, RelyX Unicem Aplicap (3M ESPE, Seefeld, Germany).…”
Section: Dentin Management: Chemical Treatments Altering the Integritmentioning
confidence: 96%